Caffeine Accelerates Emergence from Isoflurane Anesthesia in Humans: A Randomized, Double-blind, Crossover Study. (November 2018) - Fong, Robert; Wang, Lingzhi; Zacny, James P.; Khokhar, Suhail; Apfelbaum, Jeffrey L.; Fox, Aaron P.; Xie, Zheng
Editor's Perspective: What We Already Know about This Topic: Caffeine may speed anesthetic emergence What This Article Tells Us That Is New: The authors tested the hypothesis that caffeine speeds anesthetic emergence Volunteers anesthetized with isoflurane were given caffeine (equivalent to 7.5 mg base) or placebo in a blinded crossover trial When given caffeine, the volunteers emerged more quickly and at a higher isoflurane concentration Background: There are currently no drugs clinically available to reverse general anesthesia. We previously reported that caffeine is able to accelerate emergence from anesthesia in rodents. This study was carried out to test the hypothesis that caffeine accelerates emergence from anesthesia in humans. Methods: We conducted a single-center, randomized, double-blind crossover study with eight healthy males. Each subject was anesthetized twice with 1.2% isoflurane for 1 h. During the final 10 min of each session, participants received an IV infusion of either caffeine citrate (15 mg/kg, equivalent to 7.5 mg/kg of caffeine base) or saline placebo. The primary outcome was the average difference in time to emergence after isoflurane discontinuation between caffeine and saline sessions. Secondary outcomes included the end-tidal isoflurane concentration at emergence, vital signs, and Bispectral Index values measured throughout anesthesia and emergence. Additional endpoints related to data gathered from postanesthesia psychomotor testing. Results: All randomized participants were included in the analysis. The mean time to emergence with saline was 16.5 ± 3.9 (SD) min compared to 9.6 ± 5.1 (SD) min with caffeine ( P = 0.002), a difference of 6.9 min (99% CI, 1.8 to 12), a 42% reduction. Participants emerged at a higher expired isoflurane concentration, manifested more rapid return to baseline Bispectral Index values, and were able to participate in psychomotor testing sooner when receiving caffeine. There were no statistically significant differences in vital signs with caffeine administration and caffeine-related adverse events. Conclusions: Intravenous caffeine is able to accelerate emergence from isoflurane anesthesia in healthy males without any apparent adverse effects. Abstract : The authors tested the hypothesis that caffeine speeds anesthetic emergence. Volunteers anesthetized with isoflurane were given caffeine (equivalent to 7.5 mg base) or placebo in a blinded crossover trial. When given caffeine, the volunteers emerged more quickly and at a higher isoflurane concentration.